Report Analysis and Use of Tahfizh Assessment Results at Tahfizh Qur'an Elementary School Taman Cinta Al-Qur'an in South Kalimantan: Analisis Laporan dan Penggunaan Hasil Penilaian Tahfizh pada SD Tahfizh Qur’an Taman Cinta Al-Qur’an di Kalimantan Selatan - Dina Hermina; Nuril Huda; Firdaus, Firdaus (Universitas Muhammadiyah Sidoarjo, 2023)
Report analysis and use of the results of the tahfizh assessment at SD Tahfizh Qur’an Taman Cinta Al-Qur'an in Barito Kuala Regency, South Kalimantan Province. The method used in this research is descriptive evaluative qualitative method. The subjects studied were school principals, curriculum deputy heads, tahfizh coordinators, tahfizh teachers, grade IV and grade V students. Data collection techniques were by means of observation, interviews and semi-structures. Data processing techniques are carried out by reducing data, displaying data and concluding. Checking the validity of the data in this study used triangulation of sources and techniques. Based on the results of the research, it shows that the evaluation of the Tahfizh Qur'an program at SDTQ Taman Cinta Al-Qur'an; (1) The planning is through the school's vision and mission. (2) The implementation is by way of memorizing, tahsin recitations, tasmi', muroja'ah, and connecting verse tests. (3) The evaluation is carried out by means of per-juz evaluation, per-letter evaluation, sima'an evaluation, weekly evaluation, monthly evaluation and special evaluation.